Penetrating Orbital-Cranial Injuries Management in a Limited Resource Hospital in Latin America. Issue 4 (December 2015) - Estebanez, Glyn; Garavito, Diana; López, Laura; Ortiz, JuanCarlos; Rubiano, Andrés M.
Penetrating orbital-cranial injuries (POCIs) are difficult cases especially in hospitals in low-middle-income countries (LMIC) where resources are limited. We present a case series of POCI managed in a university hospital in such scenario. A retrospective case series was conducted including patients with POCI in 2011. Mechanism of injury, Glasgow Coma Scale score, imaging, medical and surgical management, complications, and Glasgow Outcome Scale (GOS) score were analyzed. A total of 30 patients with penetrating orbital injuries were admitted from March 2011 to December 2011. Of this group, only four patients were diagnosed with cranial penetration. Computed tomography (CT) angiography revealed orbital fractures and injury to frontal, temporal, or occipital lobes. Urgent craniotomy with isolation of ipsilateral carotid artery was performed. GOS score at discharge was 5 in three patients and 4 in one patient. POCIs are not uncommon in hospitals of LMIC. In such scenarios, a standard approach with CT angiography and early neurosurgical intervention results in good outcome.